Pengaruh Self-Efficacy, Motivasi, Dan Komitmen Karyawan Terhadap Kinerja Karyawan Di Elizabeth International Hotel And Business School - I Gusti Aju Maitri Wati; Luh Komang Candra Dewi; L. K. Herindiyah Kartika Yuni (Warmadewa Management and Business Journal (WMBJ), 2026)
This study aims to analyze the influence of self-efficacy, motivation, and employee commitment on employee performance at Elizabeth International Hotel and Business School. The population in this study includes all employees at LPK Elizabeth International Hotel and Business School, totally 85 individuals. The sampling technique used in this research is a census or saturated sampling technique. The data analysis techniques employed include validity testing, reliability testing, classical assumption testing, and multiple regression analysis. The results of the analysis indicate that 1) Self-efficacy has a positive and significant effect on employee performance; 2) Motivation has a positive and significant effect on employee performance; 3) Commitment has a positive effect on employee performance; 4) Self-efficacy, motivation, and employee commitment simultaneously have a significant effect on employee performance at Elizabeth International Hotel and Business School. Based on these findings, it is recommended that the management of Elizabeth International Hotel and Business School enhance self-efficacy, motivation, and employee commitment in efforts to improve employee performance.